Molecular mechanisms of Cys-loop ion channel receptor modulation by ivermectin - Lynagh, Timothy; Lynch, Joe (Frontiers in Molecular Neuroscience, 2012)
Ivermectin is a gold standard anthelmintic drug that works by potently depressing neuronal activity and muscular contractility in arthropods and nematodes. At the molecular level, ivermectin activates inhibitory glutamate-gated chloride channels (GluClRs), which are found exclusively in invertebrates, at nanomolar concentrations. These receptors belong to the pentameric Cys-loop receptor family of ligand-gated ion channels. Higher (micromolar) concentrations of ivermectin also activate and/or modulate vertebrate Cys-loop receptors, including the excitatory nicotinic acetylcholine receptor and the inhibitory GABA type-A and glycine receptors (GlyRs). In the last twelve months, an X-ray crystal structure of ivermectin complexed with the C. elegans α GluClR demonstrated that ivermectin binds to the transmembrane region of the receptor in a cleft formed at the interface of adjacent subunits. This study also identified three critical hydrogen bonds that were thought to attach ivermectin to its site. Site-directed mutagenesis and voltage-clamp electrophysiology have also been employed to probe the binding sites for ivermectin in the α1 GlyR. This study has raised doubts as to whether the hydrogen bonds are important for high ivermectin potency in either GlyRs or GluClRs. Due to its lipophilic nature, it is likely that ivermectin accumulates in the membrane and binds reversibly (i.e., weakly) to its target site. Several lines of evidence suggest that ivermectin opens the channel pore via a structural change that is distinct from that induced by the endogenous neurotransmitter agonist. Finally, voltage-clamp fluorometry has demonstrated that ivermectin induces a global conformational change that propagates to the neurotransmitter binding site, thus suggesting a mechanism by which ivermectin may potentiate neurotransmitter-gated currents. Together, this information provides new insights into the mechanisms of action of this clinically important drug.